Tingkat Literasi Zakat pada Mahasiswa terhadap Minat Pembayaran Zakat Era Digital - Ayuningtias, Zhenika Devi; Syaharani, Syihan Maulaya; Maulidah, Nurul Hikmah; Haq, Hasna Hamidatul; Aisy, Diamantin Rohadatul (Al Maal: Journal of Islamic Economics and Banking, 2024)
This research aims to examine and determine the level of zakat literacy among students regarding their interest in paying zakat in the digital era.  The type of approach in this research is quantitative using primary data obtained through a questionnaire based on respondents' answers which the researcher distributed to students at the FEB UIN Syarif Hidayatullah Jakarta Campus.  The analytical method in this research uses the Structural Equation Modeling (SEM) application using the analytical tool used in this research, SmartPLS version 4 software. The results of this research show that interest in paying zakat in the digital era is significantly influenced by the level of zakat literacy among students.  This research proves that every change in students' zakat literacy will affect the level of interest in paying zakat. Based on (R2), it can be seen that the R-Square value for Y1 Interest in Paying Zakat is 0.232, meaning that the influence of X1 Zakat Literacy on Interest in Paying Zakat is 23.2% (moderate) and 76.8% is explained by variables outside the research.  Meanwhile, the Adjusted R-Square value has a value of 0.224 or 24% which is included in the weak category.